ANALISIS PENGARUH KETIMPANGAN GENDER TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI RIAU TAHUN 2010-2019 - Desmi, Roslinda; Harlen, Harlen; Rahmita, Budiartiningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study is entitled Analysis of the Effect of Gender Inequality on Economic Growth in Riau Province in 2010-2019. This study aims to look at gender inequalities and the effect of health, education, and labor force participation rates on economic growth from 2010 to 2019. To determine whether or not health, education, and the level of labor force participation effect economic growth, the analysis used in this is multiple linear regression analysis. The data used in this research is secondary data. Obtained from related agencies in Pekanbaru City , namely the Pekanbaru City Central Statistics Agency. The results showed that the health variable had a significant negative effect on economic growth, the education variable had a significant positive effect on economic growth and the labor force participation rate variable had a positive effect on economic growth in Riau Province.Keywords : Health Education, Labor Force Perticipation Rate, Economic Growth